2012
DOI: 10.1111/j.1600-0706.2012.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Can limiting similarity increase invasion resistance? A meta‐analysis of experimental studies

Abstract: Synthesis We used meta‐analyses to examine experimental evidence that functional similarity between invaders and resident communities reduces invasion. We synthesized evidence from studies that experimentally added seed to resident communities in which the functional group composition had been manipulated. We found communities containing functionally similar resident species reduced invasion of forb but not grass invaders. However, experimental design dramatically influenced the results – with evidence for lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 62 publications
5
83
0
Order By: Relevance
“…This is consistent with a number of recent empirical findings which show absent or very weak signatures of limiting similarity (e.g. Kunstler et al 2012;Bennett et al 2013;Price & P€ artel 2013).…”
supporting
confidence: 93%
“…This is consistent with a number of recent empirical findings which show absent or very weak signatures of limiting similarity (e.g. Kunstler et al 2012;Bennett et al 2013;Price & P€ artel 2013).…”
supporting
confidence: 93%
“…Funk et al (2008) suggested that strategically increasing the abundance of native plant species with functional traits similar to nonnative plant species can increase biotic resistance to invasion, through limiting similarity. However, a meta-analysis of experimental studies testing the effect of functional similarity on invasion success, only found evidence for this in synthetic experimental assemblages, and not in more 'natural' removal experiments (Price and Pärtel 2013). Hence ''restoration through reassembly'' (Funk et al 2008) may only be useful as a guiding principle when communities are built de novo.…”
Section: Moving From Compositional To Functional Goals In a Changing mentioning
confidence: 99%
“…In the study grassland, however, functional group biomass was pervasive in determining its ability to control expansion by established exotic species. Thus, life-form similarity did not emerge as a relevant aspect of invasion patterns in this removal experiment (Price & P€ artel 2013). Low compensatory responses to removal of dominant native grasses suggested that mechanisms other than resource competition, including temporal niche separation, recruitment limitation and facilitation, all influenced community dynamics (Stachowicz & Tilman 2005;Gilbert, Turkington & Srivastava 2009;Roscher et al 2009).…”
Section: I F F E R E N T I a L R E S P O N S E S O F E X O T I C P mentioning
confidence: 82%
“…It has been argued that functional similarity between resident and invader species may influence invasion success (Fargione, Brown & Tilman 2003;Hooper & Dukes 2010;Price & P€ artel 2013). Accordingly, invasion would be more likely by species sharing the same functional group (or lifeform) with species being lost (Symstad 2000;Emery 2007;Mwangi et al 2007).…”
Section: I F F E R E N T I a L R E S P O N S E S O F E X O T I C P mentioning
confidence: 99%
See 1 more Smart Citation